2012
DOI: 10.1371/journal.ppat.1002635
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania Induces Survival, Proliferation and Elevated Cellular dNTP Levels in Human Monocytes Promoting Acceleration of HIV Co-Infection

Abstract: Leishmaniasis is a parasitic disease that is widely prevalent in many tropical and sub-tropical regions of the world. Infection with Leishmania has been recognized to induce a striking acceleration of Human Immunodeficiency Virus Type 1 (HIV-1) infection in coinfected individuals through as yet incompletely understood mechanisms. Cells of the monocyte/macrophage lineage are the predominant cell types coinfected by both pathogens. Monocytes and macrophages contain extremely low levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 85 publications
3
31
0
Order By: Relevance
“…Several studies have shown that infection of myeloid cells with Leishmania parasites promotes HIV replication [6], [7], [8]. Equally, HIV not only promotes Leishmania uptake by macrophages [9], but also increases parasite replication in monocytes [10]; this is in agreement with the observation of increased parasitemia in VL/HIV patients [11].…”
Section: Introductionsupporting
confidence: 75%
“…Several studies have shown that infection of myeloid cells with Leishmania parasites promotes HIV replication [6], [7], [8]. Equally, HIV not only promotes Leishmania uptake by macrophages [9], but also increases parasite replication in monocytes [10]; this is in agreement with the observation of increased parasitemia in VL/HIV patients [11].…”
Section: Introductionsupporting
confidence: 75%
“…Primary human monocytes were isolated from the peripheral blood buffy coats by positive selection using MACS CD14+ beads as previously described [64] or by a Dynabeads Untouched Human Monocytes kit according to the manufacturer's protocol. For macrophage differentiation, monocytes were matured for seven days in RPMI medium containing 10% FCS, Pen/Strep antibiotics and 5 ng/ml human recombinant GM-CSF (R&D Systems) before use in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the mechanism whereby HIV infection acts as an aggravating factor in metastatic leishmaniasis may be far more complex than a simple collapse of the CD4 compartment. Indeed, Leishmania survive better in cells exposed to HIV and vice versa [34,35]. This creates a situation where PRR crosstalk as well as genetic polymorphisms in these PRRs (Box 3) should be considered as key parameters of leishmanial pathogenesis.…”
Section: Metastatic Risk Factors In the Hostmentioning
confidence: 99%